The Interaction between Soil Nutrients and Leaf Loss during Early Establishment in Plant Invasion - Elizabeth A. Leger; Katherine M. Howe; Jessica Gurevitch; Eliza Woo; Jonathan Hickman; Isabel W. Ashton; Manuel Lerdau (Forest Science, 2007)
Nitrogen availability affects both plant growth and the preferences of herbivores. We hypothesized that an interaction between these two factors could affect the early establishment of native and exotic species differently, promoting invasion in natural systems. Taxonomically paired native and invasive species (Acer platanoides, Acer rubrum, Lonicera maackii, Diervilla lonicera, Celastrus orbiculata, Celastrus scandens, Elaeagnus umbellata, Ceanothus americanus, Ampelopsis brevipedunculata, and Vitis riparia) were grown in relatively high-resource (hardwood forests) and low-resource (pine barrens) communities on Long Island, New York, for a period of 3 months. Plants were grown in ambient and nitrogen-enhanced conditions in both communities. Nitrogen additions produced an average 12% initial increase in leaf number of all plants. By the end of the experiment, invasive species outperformed native species in nitrogen-enhanced plots in hardwood forests, where all plants experienced increased damage relative to control plots. Native species experienced higher overall amounts of damage in hardwood forests, losing, on average, 45% more leaves than exotic species, and only native species experienced a decline in growth rates (32% compared with controls). In contrast, in pine barrens, there were no differences in damage and no differences in performance between native and invasive plants. Our results suggest that unequal damage by natural enemies may play a role in determining community composition by shifting the competitive advantage to exotic species in nitrogen-enhanced environments.